The Impact of Commercial Rainfall Index Insurance: Experimental Evidence from Ethiopia. Issue 4 (11th February 2020) - Ahmed, Shukri; McIntosh, Craig; Sarris, Alexandros
Abstract : We present the results of an experiment introducing commercial rainfall index insurance into drought‐prone farming cooperatives in Amhara Region, Ethiopia. We provided a market‐priced rainfall deficit insurance product through producer cooperatives and tested a number of potential ways to kick start private demand. Take up of the insurance at market prices is very low, between 0.5% and 3% across seasons. When we use a randomized experiment to distribute small free insurance contracts to farmers, 39% of subsidized individuals enroll but this fails to stimulate input use, yields, or income, nor does it enhance demand in subsequent seasons. A training and promotion on the product improves uptake and willingness to pay but also does not improve farming outcomes. We conclude with a case study of our efforts to interlink index insurance with credit for agricultural inputs.